2016
DOI: 10.4314/afrrev.v10i5.13
|View full text |Cite
|
Sign up to set email alerts
|

A review on courtyard design criteria in different climatic zones

Abstract: The application of courtyard in a building design can contribute meaningfully towards achieving a passive building with high energy efficiency, only when its design criteria are not ignored. It is on this note that this study examined the design criteria for courtyard in different climatic zones. The courtyard design criteria with respect to form and its effects on wind movement and lighting in different climatic zones is investigated based on literature review. Journals, Conference Papers and Books were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The courtyard acts as a passive strategy to enhance daylight, thermal comfort, and ventilation in the interior spaces attached to it. Daylighting and ventilation through the courtyard generally depend on the form, area, proportions, orientation, shading elements, vegetation, built open ratio, aspect ratio, shape, perimeter ratio, and the water body (Markus 2016). Besides thermal comfort, ventilation, and daylighting, courtyards also have social and psychological effects.…”
Section: Traditional Courtyard Housesmentioning
confidence: 99%
See 1 more Smart Citation
“…The courtyard acts as a passive strategy to enhance daylight, thermal comfort, and ventilation in the interior spaces attached to it. Daylighting and ventilation through the courtyard generally depend on the form, area, proportions, orientation, shading elements, vegetation, built open ratio, aspect ratio, shape, perimeter ratio, and the water body (Markus 2016). Besides thermal comfort, ventilation, and daylighting, courtyards also have social and psychological effects.…”
Section: Traditional Courtyard Housesmentioning
confidence: 99%
“…Besides thermal comfort, ventilation, and daylighting, courtyards also have social and psychological effects. Appropriate daylight affects the psychology of the user and the visual comfort in the adjoining spaces (Markus 2016). Moreover, it segregates the social spaces, giving habitants a view of the sky and fresh air and bringing them closer to the outer environment.…”
Section: Traditional Courtyard Housesmentioning
confidence: 99%
“…Hence, the courtyard's length-to-height ratio should be optimized to achieve heat mitigation [14]. The proportions and dimensions of the courtyard will significantly increase its capacity for improved environmental efficiency [15]. While considering major characteristics of the courtyard, which includes optimal size and shape and shading pattern.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, the courtyard, which incorporates optimized design components and natural elements, acts as a microclimatic modifier [14]. While examining the behavior of courtyard form in different climatic zones, it was observed that all climatic zones have nearly the same design criteria, but variables such as the suitable form, sizes, and proportions are highly dependent on the climatic context of each zone [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…And it is becoming more and more difficult to ignore the issues of microclimatic performance of the architectural design space(s). Recent studies in PAD have emphasized that the courtyard is a passive design element, and its microclimatic performance should be investigated (Tablada et al, 2005;Akande 2010;and Markus 2016a).…”
Section: Introductionmentioning
confidence: 99%